On Some Grammatical Peculiarities of Indian English - Harutyunyan, Kristine; Harutyunyan, Rafayel (Armenian Folia Anglistika, 2019)
English is a lingua franca that unites all the nations in the world. It is not only the language of universal communication but also a language to access the scientific world, international business and the world of entertainment as many of the world’s top films, books and songs are published and produced in English. The English that people use for social interaction in India differs considerably from the English spoken in other regions of the world in terms of vocabulary, syntax and other aspects of language. Thus, the aim of the present article is to investigate Indian English as a distinctive variety of English and to show how Indians have customized English in various ways, and willingly or unwillingly, have better suited it to their needs. We also discuss some grammatical peculiarities of Indian English used or experienced in different settings.
Keywords: Indian English; linguistic variety/variation; social interaction; customization of English; grammatical peculiarities